IMPLEMENTASI METODE CERTAINTY FAKTOR DALAM SISTEM PAKAR UNTUK DIAGNOSA KERUSAKAN LAPTOP - Widianto, Septian Cahyo; Widada, Bebas; Sandradewi, Kumaratih; Remawati, Dwi (STMIK Sinar Nusantara, 2025)
Expert systems have been used in various fields. With the aim of helping users solve the problems they face. This study presents the application of the Certainty Factor (CF) method in an expert system designed to diagnose laptop damage based on symptoms experienced by users. This system aims to help technicians and general users identify potential laptop malfunctions with better accuracy. The expert system developed combines a comprehensive knowledge base consisting of various laptop components and their common problems. The CF method calculates the probability of damage by combining expert knowledge with user-reported symptoms. Through a series of tests conducted on several brands of laptops with various types of malfunctions, the system showed outstanding performance. The results showed 87% accuracy in diagnosing hardware problems such as motherboard failure, RAM damage, and hard drive malfunction.